(untitled) (Perspectivas em Ciência da Informação, 2009)
Citation analysis of the bibliography used in the elaboration of academic dissertations can support the decision-making process in collection development in the university library. The analysis of the type of materials, its obsolescence, its languages, and the titles of journals cited will make it possible to improve the distribution of the budget; to establish guidelines for storage; to determine the composition of the core collection of journals; and to identify languages in which the bibliographical materials should be acquired.